Some aspects of the wind in the northern area of the depression of Transylvania - Sorocovschi V. (Acta climatologica, 1996)
Összefoglalás - A jelen tanulmány az Erdélyi Medence északi részén előforduló talajmenti és magaslati szél egyes vonásait mutatja be. A szél paramétereinek az elemzése 5 meteorológiai állomás (Torda, Kolozsvár, Dézs, Beszterce és Marosvásárhely) és a Kolozsvári Aerológiai Állomás által szolgáltatott, 1961 és 1980 között feljegyzett adatok alapján történt. A szél irányának és sebességének az évi, évszaki és havi középértékeit a talajszinten és az 5 standard izobár szinten számítottuk ki. A felszín morfológiai sajátosságai és ennek a Kárpátok vonulatához viszonyított elhelyezkedése meghatározza a talajmenti szél paramétereinek regionális jellemzőit. A Kárpátok vonulatának a légmozgásra gyakorolt hatása körülbelül 3000 m magasságig érződik, fölötte a nyugati széljárás jellemző. Summary - The study presents some aspects of the ground level and altitudinal wind in the northern area of the Depression of Transsylvania. The analysis of the wind parameters is based on the data provided by 5 meteorological stations (Turda, Cluj-Napoca, Dej, Bistrija and Tárgu-Mure$) and the Cluj-Napoca Aerological Observatory, covering the interval between 1961-1980. The annual, seasonal and monthly average values of the direction and speed of the wind at ground level and at the five standard isobaric levels have been calculated. The regional differences of the wind parameters at ground level are affected by the morphologic peculiarities of the area and by its position in the vicinity of the Carpathian bow. In the altitude the influence of the Carpathians upon the circulation of the air is felt as high as 3000 m. Above this level the western circulation is predominant.